2017
DOI: 10.1039/c7cp04232a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physisorption of inert organic molecules on Au(111) surface electronic states

Abstract: The modification of the Au(111) Shockley surface state (SS) by an n-alkane molecule (n-tetratetracontane) monolayer was observed by angle-resolved ultraviolet photoemission spectroscopy. Although there is little chance of chemical interaction in this ideal physisorption system, the volume of the Fermi surface of the SS was significantly reduced accompanied by the formation of large interface electric dipoles. Moreover, Rashba splitting of the SS by spin-orbit interactions was slightly increased upon n-tetratet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Using n-tetratetracontane on Au(111) as a prototypical physisorbed system, Mizushima et al observed a work-function reduction due to pushback in excess of 1 eV. [215] They also provided a more detailed description of the interaction, involving, e.g., an adsorbate-induced modification of the Shockley surface state of the metal in combination with system-specific interfacial charge rearrangements. [215] These are rationalized through electron sharing between substrate and adsorbate involving bonding and antibonding CH states in the metal-molecule bond [216] and by including the hybridization between metal d-bands and unoccupied molecular orbitals.…”
Section: Pauli Pushback (Cushion Effect)mentioning
confidence: 99%
See 1 more Smart Citation
“…Using n-tetratetracontane on Au(111) as a prototypical physisorbed system, Mizushima et al observed a work-function reduction due to pushback in excess of 1 eV. [215] They also provided a more detailed description of the interaction, involving, e.g., an adsorbate-induced modification of the Shockley surface state of the metal in combination with system-specific interfacial charge rearrangements. [215] These are rationalized through electron sharing between substrate and adsorbate involving bonding and antibonding CH states in the metal-molecule bond [216] and by including the hybridization between metal d-bands and unoccupied molecular orbitals.…”
Section: Pauli Pushback (Cushion Effect)mentioning
confidence: 99%
“…[215] They also provided a more detailed description of the interaction, involving, e.g., an adsorbate-induced modification of the Shockley surface state of the metal in combination with system-specific interfacial charge rearrangements. [215] These are rationalized through electron sharing between substrate and adsorbate involving bonding and antibonding CH states in the metal-molecule bond [216] and by including the hybridization between metal d-bands and unoccupied molecular orbitals. [217] In the context of Pauli pushback, one also has to keep in mind that it is massively reduced, when the metal substrate is not clean (e.g., covered by a thin hydrocarbon layer) or when it is intentionally or unintentionally covered with a thin nonmetallic layer (e.g., an oxide).…”
Section: Pauli Pushback (Cushion Effect)mentioning
confidence: 99%
“…They are smaller than the work function reductions usually found for systems that interact only via Pauli pushback, which for inert organic molecules on gold often amounts to up to 1 eV. 76 , 77 An almost zero net interface dipole has been observed for the low-coverage phase of hexaazatriphenylene-hexanitrile (HATCN) on Ag(111). 78 However, in contrast to HATCN/Ag(111), for TAPP-CF 3 /Au(111), we find that the molecule is ≈0.2 e positively charged (when applying the Mulliken charge partitioning scheme, see the Supporting Information ), while the LUMO remains empty (see Figure 6 a).…”
Section: Resultsmentioning
confidence: 99%
“…They are smaller than the work function reductions usually found for systems that interact only via Pauli pushback, which for inert organic molecules on gold often amounts to up to 1 eV. 76,77 An almost zero net interface dipole has been observed for the low-coverage phase of hexaazatriphenylene-hexanitrile (HATCN) on Ag(111). 78 However, in contrast to HATCN/Ag(111), for TAPP-CF 3 /Au(111) we find that the molecule is ≈ 0.2e positively charged (when applying the Mulliken charge partitioning scheme, see supporting informa-tion), while the LUMO remains empty (see Figure 6a).…”
Section: Electronic Structure Of Tapp-cf 3 On Au(111)mentioning
confidence: 99%